Awareness on diabetes and its ocular complications among first year medical undergraduates - Charles, Lydia; Kumaresan, Vinisha; Puri, Sanjeev Kumar (International Journal of Advances in Medicine, 2022)
Background: Diabetes mellitus has nowadays become a world-wide health problem. The aim of this study is to bring awareness among medical students on ocular complications caused due to diabetes mellitus. Methods: A questionnaire-based, cross-sectional study was conducted among 250 first year medical undergraduate students. A simple and easily understandable questionnaire was drafted and validated. This questionnaire tested their knowledge about diabetes and its ocular complications. Results: Out of 250 students, 210 have participated in the study. Out of 210 students, 40.48% (85/210) have heard about diabetes mellitus but they did not know that it can affect the eye and can lead to blindness. 42.86% (90/210) were aware about the disease, its potential to cause vision threatening complications and ways to prevent these complications. 16.67% (35/210) were not aware about diabetes mellitus. Conclusions: The awareness about diabetes mellitus is high among students. But awareness on ocular complications due to diabetes is very low in students. So, it is necessary to educate every single student about the complications of diabetes and how it affects the eye. It is important to implement and conduct awareness programs to increase awareness among students. It is important to educate the students on periodic eye check-up to prevent complications.